Evaluasi Keadaan Continuance Intention to Use dan Citizen Support pada Implementasi Layanan Website Pusat Pelayanan Pengaduan Masyarakat (P3M) Kabupaten Sidoarjo - Lili Kordina; Widhy Hayuhardhika Nugraha Putra; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Website of P3M Sidoarjo Regency version 2018 is a renewal version of the Sidoarjo Regency P3M website which acts as the main media to accommodate aspirations, criticisms, suggestions and complaints from the Sidoarjo community. However, website of P3M Sidoarjo Regency version 2018 does not interest the public, it is seen from the number of complaints that enter through social media more than the website of P3M Sidoarjo Regency version 2018. Evaluation needs to be done to improve the Sidoarjo P3M website so that it can increase interest in using the website from peoples. Evaluation is based on the concept of continuance intention to use and citizen support. The variables used are perceived usefulness, perceived ease of use, continuance intention to use, and citizen support. Data retrieval is done by interviewing and online questionnaires to 70 respondents. The results showed that perceived usefulness belongs to high category (62.00%), perceived ease of use belongs to very high category (77.48%), continuance intention belongs to high category (72, 60%), and citizen support belongs to medium category (54.10%), so that the total average value of all variables is included in the high category (66.54%). From the results of the research, a website improvement recommendation was developed to increase sidoarjo comumunity interest in using the website of P3M Sidoarjo Regency version 2018.